Adaptaciones Curriculares en la dislexia en estudiantes de tercer grado de la Unidad Educativa Antonio Neumane de Santo Domingo, período 2023-2024 - Monar Torres, Dayana Nicolle (2024)
Dyslexia is a specific learning disorder of neurobiological origin, it is characterized by the difficulties in the precision and fluency when recognising written words, as well as by problems in decoding and spelling. Therefore, it is essential to implement adaptive teaching strategies, which schools and educational institutions are obliged to develop and execute. Although these measures have been implemented, some deficiencies are still found regarding specialized resources and strategies, such as curricular adaptations. That is why the objective of this paper is to analyse curricular adaptations to give treatment to dyslexia in third grade students. For the analysis it was implemented a qualitative approach, since the relevant information of the variables was carefully investigated, identified and selected; Also, we used a non-experimental design because no variables were manipulated; the methods used were scientific, inductive, analytical, synthetic and descriptive; the interview and observation sheet served to collect relevant information in an orderly and effective manner in a sample population of five students and one teacher. It was found that, although the teacher had implemented curricular adaptations to the curriculum, these did not meet all the characteristics investigated, which generated inconsistencies in their execution, harming students with dyslexia. In addition, it was evidenced that the educator had difficulty recognizing the basic elements of dyslexia, and such unfamiliarity affects the early identification of subtle or atypical cases of the disorder. In conclusion, curricular adaptations for students with dyslexia are crucial because they facilitate their access to learning through inclusive and personalized educational strategies which ensure that all students have the opportunity to achieve their maximum academic and personal potential. However, the lack of specific training and adequate resources for teachers can limit the effectiveness of such adaptations.